(untitled) (Plant Tissue Culture and Biotechnology, 2015)
The vascular system of plants consists fundamentally of two functional cell types, phloem and xylem. Phloem forms an extensive conduit for the dynamic long?distance transport of a diverse range of macromolecular signals that are required for plant development and defense mechanisms. Vascular tissues contain low levels of signaling peptide molecules, which are technically difficult to identify and characterize. We identified low molecular weight peptides from the phloem sap of Chinese Long cucumber using nano?LC?ESI?MS/MS with high SEQUEST scores. Bioinformatics analyses predicted their biological functions as signaling peptides and/or antimicrobial peptides. Here, we selected two peptides (Cupep?1 and Cupep?2), with highly SEQUEST score, to be synthesized and functionally investigated. Cupep?1 synthetic peptide showed a robust antimicrobial activity against Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Bacillus subtilis and Candida albicans. These results potentiate the use of Cupep?1 peptide as a natural food preservative. We also show that the Cupep?2 peptide was able to conditionally change plant cell differentiation. Thus we suggest a role of Cupep?2 in plant development. Plant Tissue Cult. & Biotech. 25(1): 71-85, 2015 (June)